Value-free science? : ideals and illusions - Kincaid, Harold, 1952-; Dupré, John; Wylie, Alison (Oxford University Press, 2007)
The contributors to this volume investigate where and how values are involved in science, and examine the implications of this involvement for ideals of objectivity.